(untitled) (World Bulletin of Social Sciences, 2023)
In the article were analyzed the processes of modernization of public administration in the early years of Independence of Uzbekistan. Based upon various scientific and political sources, the author elucidates the key trends and factors that determined the directions of implementation of the modernization of the executive power in Uzbekistan in the early years of Independence.